Intramuscular artemether vs intravenous quinine: an open, randomized trial in Malawian children with cerebral malaria. - Taylor, T; Wills, B; Courval, J; Molyneux, M (1998)
OBJECTIVES: To compare artemether (by intramuscular injection) and quinine (by intravenous infusion) as treatments for cerebral malaria in African children. METHODS: An open, randomized trial conducted at the Queen Elizabeth Central Hospital in Blantyre, Malawi. This trial was part of a multicentre study designed to determine if treatment with artemether would significantly lower mortality rates compared with quinine. Data from 83 artemether recipients and 81 quinine recipients are reported here. RESULTS: Overall mortality rates and coma resolution times were not significantly different in the two treatment groups. Parasite and fever clearance times were significantly more rapid in the artemether recipients. Analyses which took into account the possible confounding variables did not significantly alter the findings of these unadjusted analyses. CONCLUSION: These results do not suggest that treatment with artemether would confer a survival advantage in children with life-threatening malaria. The power and precision of the estimated treatment effects of artemether would be enhanced by a meta-analysis of all relevant clinical trials.